STUDI LITERATUR: PENGEMBANGAN MODEL PEMBELAJARAN BERBASIS MASALAH MATEMATIKA DENGAN BANTUAN LEMBAR KERJA INTERAKTIF (LKPD) UNTUK MENINGKATKAN PIKIRAN KRITIS DAN KREATIF DI SEKOLAH MENENGAH ATAS (SMA) : Bahasa Indonesia - Yunitajayanti, Mawiti; Herpratiwi, Hepratiwi; Nurhanurawati, Nurhanurawati; Sugeng Sutiarso , Sugeng Sutiarso (UNDIKMA, 2026)
Educational developments in the 21st century demand the strengthening of higher-order thinking skills, particularly critical and creative thinking in mathematics education. The reality is that learning is still dominated by conventional approaches that focus on procedures, thereby failing to sufficiently develop students’ analytical skills. On the other hand, technological advancements open up opportunities for innovation through digital platform-supported e-worksheets. The Problem-Based Learning (PBL) model is relevant because it emphasizes the resolution of authentic problems that encourage deep thinking. This study aims to analyze and synthesize research findings related to the development of PBL-based mathematics worksheets supported by Liveworksheet in enhancing the critical and creative thinking of MTs students. The method used is a Systematic Literature Review (SLR) following the PRISMA procedure. Data were obtained from Google Scholar, DOAJ, ERIC, SINTA journals, and Scopus for the period 2020–2025, with 10 selected articles. The results of the study indicate that PBL is effective in enhancing critical thinking through analysis and problem-solving. The integration of Liveworksheet enhances interactivity and learning feedback. Research remains focused primarily on critical thinking, while the integration of critical and creative thinking remains limited. It can be concluded that PBL-based worksheets supported by Liveworksheet have the potential to effectively and adaptively enhance the critical and creative thinking skills of MTs students.